Nerve Stimulation by Triboelectric Nanogenerator Based on Nanofibrous Membrane for Spinal Cord Injury - Xu, Chaoling; Zeng, Fan; Wu, Danyu; Wang, Pang; Yin, Xiaoling; Jia, Bin (Frontiers in Chemistry, 2022)
Spinal cord injury (SCI) is a devastating and common neurological disorder that is difficult to treat. The pain can sustain for many years, making the sufferer extremely painful. Nerve stimulation was first reported half a century ago as a treatment for neuropathic pain. Since then, the method of electrical stimulation through leads placed in the epidural space on the dorsal side of the spinal cord has become a valuable therapeutic tool for SCI. But nerve stimulation equipment is expensive, and the stimulator design and treatment plan are complicated, which hinders its development. In recent years, wearable and implantable triboelectric nanogenerators (TENGs) developed rapidly, and their low cost and safety have brought a new turning point for the development of nerve stimulation. Nanofibrous membrane has been proved that it is a flexible material with the advantages of ultrathin diameter, good connectivity, easy scale-up, tunable wettability, fine flexibility, tunable porosity, controllable composition and so on. In this paper, we discuss the technology of using nanofiber membrane on clothing to create TENGs to provide continuous electrical energy for nerve stimulation to treat SCI in patients by analyzing previous research.